Teaching Strategies, Geoboard Resource and Secondary School Students’ Achievement in Mathematics in Akwa Ibom State, Nigeria - Uya, Asukwo Okon (International Journal of Contemporary Studies in Education, 2023)
The The study investigated the influence of teaching strategies and geoboard resource on secondary school students’ achievement in mathematics in Oron Education Zone of Akwa Ibom State, Nigeria. The research design adopted for the study was a quasi-experimental pretest-posttest design with 4×2×2 factorial arrangement with four intact class groups. Collaborative and expository strategies were used for the experimental and control groups respectively. The population of the study consisted of 4157 Senior Secondary One (SS1) students from 19 public secondary schools in Oron in 2021/2022 academic school year. A sample size of 235 students from four schools was used for the study. The instruments used in gathering data for the study were Geometry Achievement Test (GAT) with the reliability coefficient of 0.81 established using test-retest methods. Data gathered in this study were analysed using mean and standard deviation to answer research questions, and Analysis of Covariance using pretest and posttest scores as co-variates for the three hypotheses. From the results obtained, there is a significant difference in students’ achievement in mathematics when taught using expository and collaborative strategies with and without geoboard. Students do not differ significantly in their achievement in mathematics when taught using expository and collaborative strategies with geoboard based on gender. Students taught using collaborative strategy with and without geoboard outperformed students taught using expository with and without geoboard as a resource material. It is concluded that collaborative strategy is more effective than the expository strategy in enhancing students’ achievement in mathematics and that the interactive effect of collaborative strategy with geoboard as a resource material is higher than that of geoboard with expository strategy. Based on the findings, it is recommended among others that, collaborative strategies should be frequently used in teaching mathematics and that geoboard as a resource material should be adopted in teaching mathematics at the secondary school level to enhance students’ achievement in mathematics.